2001
DOI: 10.1063/1.1326466
|View full text |Cite
|
Sign up to set email alerts
|

Microstructure and wet oxidation of low-temperature-grown amorphous (Al/Ga,As)

Abstract: Amorphous and polycrystalline compounds of ͑Ga,As͒ and ͑Al,As͒ grown at very low temperatures by molecular-beam epitaxy are characterized. The ultimate microstructure and the amount of excess arsenic incorporated in the ͑Ga,As͒ or ͑Al,As͒ layers are found to depend on the arsenic overpressure during the low-temperature growth. With lower arsenic overpressure, a polycrystalline structure prevails and less excess arsenic is observed inside the layer. In contrast, a high incorporation of excess arsenic achieved b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2001
2001
2015
2015

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 23 publications
0
1
0
Order By: Relevance
“…Equation 1 was extensively applied to many systems of III-IV semiconductors. [2][3][4][5][6][7][8][9][10][11] In particular, Choquette et al 2 and Naone and Coldren 10 have found that in the GaAs/AlAs/GaAs system the oxidation rate in the AlAs layer increases with its thickness. In order to explain the thickness dependence in the wet oxidation of AlAs, Naone and Coldren 10 proposed an interfacial energy model by considering the force balance at the junction of the oxide, AlAs and GaAs, and derived a simple relation between the contact angle, or curvature, and the thickness of the AlAs layer.…”
Section: Introductionmentioning
confidence: 96%
“…Equation 1 was extensively applied to many systems of III-IV semiconductors. [2][3][4][5][6][7][8][9][10][11] In particular, Choquette et al 2 and Naone and Coldren 10 have found that in the GaAs/AlAs/GaAs system the oxidation rate in the AlAs layer increases with its thickness. In order to explain the thickness dependence in the wet oxidation of AlAs, Naone and Coldren 10 proposed an interfacial energy model by considering the force balance at the junction of the oxide, AlAs and GaAs, and derived a simple relation between the contact angle, or curvature, and the thickness of the AlAs layer.…”
Section: Introductionmentioning
confidence: 96%